So We're Publishers Now? - Ekart, Donna F. (My University, 2009)
Librarians are increasingly responsible for publishing information to the web. What tools are out there to help create meaningful research guides for your students and faculty?
Keywords: Libraries; Research; Academia; Subject guides; Web publishing